Property, redistribution, and the status quo: a laboratory study - Konstantin Chatziathanasiou; Svenja Hippel; Michael Kurschilgen (Experimental Economics, 2020)
We report experimental evidence showing a positive effect of redistribution on economic efficiency via the self-enforcement of property rights, and identify which status groups benefit more and which less. We model an economy in which wealth is produced if players voluntarily comply with the—efficient but inequitable—prevailing social order. We vary exogenously whether redistribution is feasible, and how it is organized. We find that redistribution benefits all status groups as property disputes recede. It is most effective when transfers are not discretionary but instead imposed by some exogenous administration. In the absence of coercive means to enforce property rights, it is the higher status groups, not the lower status groups, who benefit from redistribution being compulsory rather than voluntary.
Keywords: C72; C92; D74; H23; P48; 330; Redistribution; Property; Status; Correlated equilibrium; Battle of the sexes; Experiment